Long⁃term effects of deep brain stimulation for Parkinson's disease under local or general anesthesia - Shu WANG; Meng ZHAO; Jun WANG; Xiong⁃fei WANG; Jun⁃hong PAN; Chang⁃qing LIU; Zhao LIU; Chun⁃sheng ZHANG; Xiao⁃ying ZHANG; Yi⁃xian HAN; Guo⁃ming LUAN; Yu⁃guang GUAN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2020)
Objective To compare the efficacy of local anesthesia and general anesthesia of subthalamic nucleus deep brain stimulation (STN⁃DBS) for Parkinson's disease (PD). Methods Forty PD patients who underwent bilateral STN ⁃ DBS from January 2015 to January 2018 were retrospectively analyzed. Twenty⁃two patients underwent local anesthesia and 18 patients underwent general anesthesia. Pre⁃ and post⁃operative Unified Parkinson's Disease Rating Scale⁃Ⅲ (UPDRS⁃Ⅲ), Hoehn⁃Yahr, Activities of Daily Living (ADL), Wechsler Adult Intelligence Scale (WAIS), Wechsler Memory Scale (WMS), Hamilton Depression Rating Scale (HAMD)⁃17 and Hamilton Anxiety Rating Scale (HAMA)⁃14 were used to assess the motor symptoms, daily living function, cognitive function, memory, anxiety and depression. Results The target deviation of the second electrode in general anesthesia group was lower than that in local anesthesia group [(0.98 ± 0.39) mm vs. (1.21 ± 0.35) mm; t = ⁃ 2.041, P = 0.048], the target deviation of the first electrode was not statistically significant [(0.96 ± 0.29) mm vs. (1.01 ± 0.35) mm; t = ⁃ 0.496, P = 0.623]. At 6, 12, and 24 months after surgery, the "on" and "off" UPDRS⁃Ⅲ scores (P = 0.001, for all) and Hoehn⁃Yahr (P = 0.001, for all) in the general anesthesia group and the local anesthesia group were all significantly decreased compared with baseline, ADL score significanly increased (P = 0.001, for all). There were no significant differences in "on" and "off" UPDRS⁃Ⅲ, Hoehn⁃Yahr, ADL, WAIS and WMS scores between 2 groups (P > 0.05, for all). One day after surgery, the HAMA⁃14 in the local anesthesia group was higher than baseline (P = 0.027), in the general anesthesia group, HAMD⁃17 (P = 0.008) and HAMA⁃14 (P = 0.001) scores were lower than 1 d before surgery. The HAMD⁃17 (P = 0.001, for all) and HAMA ⁃ 14 (P = 0.001, for all) of 2 groups at 6, 12 and 24 months after surgery were all lower than baseline, 1 d before and 1 d after surgery. HAMD⁃17 score in the general anesthesia group was lower than the local anesthesia group (P = 0.048). Conclusions Both general anesthesia and local anesthesia STN⁃DBS can significantly improve PD motor symptoms and quality of life, as well as relieve the depression and anxiety symptoms, without affecting cognitive function and memory. Attention should be paid to mood fluctuations in using different anesthesia during the perioperative period. Choice of anesthesia method should be based on the patient's condition and indications.